Arsenic Response of Three Altiplanic Exiguobacterium Strains With Different Tolerance Levels Against the Metalloid Species: A Proteomics Study - Castro-Severyn, Juan; Pardo-Esté, Coral; Sulbaran, Yoelvis; Cabezas, Carolina; Gariazzo, Valentina; Briones, Alan; Morales, Naiyulin; Séveno, Martial; Decourcelle, Mathilde; Salvetat, Nicolas; Remonsellez, Francisco; Castro-Nallar, Eduardo; et al. (Frontiers in Microbiology, 2019)
Exiguobacterium is a polyextremophile bacterial genus with a physiology that allows it to develop in different adverse environments. The Salar de Huasco is one of these environments due to its altitude, atmospheric pressure, solar radiation, temperature variations, pH, salinity, and the presence of toxic compounds such as arsenic. However, the physiological and/or molecular mechanisms that enable them to prosper in these environments have not yet been described. Our research group has isolated several strains of Exiguobacterium genus from different sites of Salar de Huasco, which show diferent resistance levels to As(III) and As(V). In this work, we compare the protein expression patterns of the three strains in response to arsenic by a proteomic approach; strains were grown in absence of the metalloid and in presence of As(III) and As(V) sublethal concentrations and the protein separation was carried out in 2D electrophoresis gels (2D-GE). In total, 999 spots were detected, between 77 and 173 of which showed significant changes for As(III) among the three strains, and between 90 and 143 for As(V) respectively compared to the corresponding control condition. Twenty-eight of those were identified by mass spectrometry (MS). Among these identified proteins, the ArsA (ATPase from the As(III) efflux pump) was found to be up-regulated in response to both arsenic conditions in the three strains, as well as the Co-enzyme A disulfide reductase (Cdr) in the two more resistant strains. Interestingly, in this genus the gene that codifies for Cdr is found within the genic context of the ars operon. We suggest that this protein could be restoring antioxidants molecules, necessary for the As(V) reduction. Additionally, among the proteins that change their expression against As, we found several with functions relevant to stress response, e.g. Hpf, LuxS, GLpX, GlnE and Fur. This study allowed us to shed light into the physiology necessary for these bacteria to be able to tolerate the toxicity and stress generated by the presence of arsenic in their niche.